The influence of restraint on the expansion of concrete due to delayed ettringite formation - Kawabata, Yuichiro; Ueda, Naoshi; Miura, Taito; Multon, Stéphane (Cement & concrete composites, 2021)
The influence of restraint on expansion, expansive pressure, and cracking patterns due to delayed ettringite formation (DEF) in concrete was experimentally evaluated. Especially, the expansive pressure was estimated with two approaches: calculation from the strain of the steel and direct measurement using load cells. The expansive behaviors were strongly affected by the restraint, especially in the restraint direction. The expansive pressure measured by the load cell was 1.9–3.9 MPa, which is nearly consistent with those calculated from the steel bar strain. The expansive pressure of DEF was almost the same order of magnitude as for ASR expansion, despite larger free DEF expansion than ASR. From a simplified calculation, it is estimated that the imposed DEF expansion was reduced from the stress-free expansion by approximately 80%. Although the total length of surface cracking was independent of the degree of the restraint, the distribution of surface cracks was significantly modified by the degree of the restraint. On the contrary, the inner crack pattern was similar for the restraint case while large gap formation was observed for the stress-free case.